2016
DOI: 10.1364/ol.41.005551
|View full text |Cite
|
Sign up to set email alerts
|

Drawing optical fibers from three-dimensional printers

Abstract: The temperature distribution within extrusion nozzles of three low cost desktop 3D printers are characterised using fibre Bragg gratings (FBGs) to assess their compatibility as micro-furnaces for topical fibre and taper production. These profiles show remarkably consistent distributions suitable for direct drawing of optical fibre. As proof of principle, coreless optical fibres (ϕ = 30 µm) made from fluorinated acrylonitrile butadiene styrene (ABS) and polyethylene terephthalate glycol (PETG) are drawn. Cut-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 6 publications
(5 reference statements)
1
14
0
Order By: Relevance
“…We numerically show that the proposed HC-NANF offers record low effective material loss, broad transmission bandwidth centered at 1 THz, near-zero waveguide dispersion, bend-improved performance and effectively single mode operation while the fiber design relies upon experimentally feasible and realistic fabrication parameters. This is because it has been reported that fiber geometries similar to the ones proposed here can be fabricated using the recent emerging technique of 3D printing [24,25]. Optimizing the design parameters, we predict an effective material loss of 0.05 dB/m; a confinement loss of 3.4 × 10 -4 dB/m at 1 THz; a bending loss of 10 -2 dB/m at 45 cm bending radius; a low-loss transmission band from 0.8 THz to 1.2 THz, for which the total transmission loss is below 0.095 dB/m; and a 0.6 THz flat dispersion band where the dispersion parameter β2 is less than 0.115993251 ps/THz/cm.…”
Section: Introductionmentioning
confidence: 97%
“…We numerically show that the proposed HC-NANF offers record low effective material loss, broad transmission bandwidth centered at 1 THz, near-zero waveguide dispersion, bend-improved performance and effectively single mode operation while the fiber design relies upon experimentally feasible and realistic fabrication parameters. This is because it has been reported that fiber geometries similar to the ones proposed here can be fabricated using the recent emerging technique of 3D printing [24,25]. Optimizing the design parameters, we predict an effective material loss of 0.05 dB/m; a confinement loss of 3.4 × 10 -4 dB/m at 1 THz; a bending loss of 10 -2 dB/m at 45 cm bending radius; a low-loss transmission band from 0.8 THz to 1.2 THz, for which the total transmission loss is below 0.095 dB/m; and a 0.6 THz flat dispersion band where the dispersion parameter β2 is less than 0.115993251 ps/THz/cm.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, beyond preform fabrication, drawing fiber directly from a 3D printed preform has been proposed and demonstrated by Canning et al [48], where they first used acrylonitrile butadiene styrene (ABS) to get coreless optical fibers with standard losses. Later, the same research group applied direct light processing (DLP) to obtain a glass perform [49].…”
Section: D Printed Glass Fibersmentioning
confidence: 99%
“…A more recent approach is to use 3D printing techniques. Successful 3D printed preforms and the corresponding drawn microstructured optical fibers have been reported [29][30][31]. All of these methods can be applied to realize a prototype of our SPSM PCF design.…”
Section: Fabrication Issuesmentioning
confidence: 97%